A novel marine bioinvasion vector: Ichthyochory, live passage through fish. Issue 3 (15th May 2017) - Guy‐Haim, Tamar; Hyams‐Kaphzan, Orit; Yeruham, Erez; Almogi‐Labin, Ahuva; Carlton, James T.
Abstract: Many species of Indo‐Pacific holobenthic foraminifera have been introduced and successfully established sustainable populations in the Mediterranean Sea over the past few decades. However, known natural and anthropogenic vectors do not explain how these species were introduced long distances from their origin. We present evidence for a novel marine bioinvasion vector explaining this long‐distance transport and introduction using both contemporary field and historical analyses. In 2015–2016, we found living specimens of 29 foraminiferal species in the fecal pellets of two Red Sea herbivorous rabbitfish— Siganus rivulatus and Siganus luridus in the Mediterranean. In our historical analysis, we found 34 foraminiferal species in preserved Red Sea rabbitfish specimens, dating between 1967 and 1975. In addition, we found congruent propagation patterns of the non‐indigenous rabbitfish and foraminifera, lagging 4–11 yrs between discoveries, respectively. Predation of marine benthos by non‐indigenous fish, followed by incomplete digestion and defecation of viable individuals, comprise the main introduction vector of these organisms into novel environments.